ESD - Voldman, Steven H. (Wiley, 2015)
Provides a clear picture of layout and design of digital, analog, radio frequency and power applications for protection from electrostatic discharge, electrical overstress, and latchup phenomena from a generalist perspective and design synthesis practices.